Food Insecurity Among International Post-Secondary Students Studying on a Canadian Campus: A Qualitative Description Study - Hanbazaza, Mahitab; Kebbe, Maryam; Perez, Arnaldo; Ball, Geoff DC; Farmer, Anna P.; Maximova, Katerina; Willows, Noreen D. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
Enrollment of international post-secondary students is increasing across Canadian campuses. International post-secondary students may experience challenges in accessing nutritious foods that meet their dietary needs and food preferences. These challenges can pose negative impacts on their health, well-being, and academic achievement. Our aim was to describe international post-secondary students’ perceptions of (1) challenges to attaining food security and (2) consequences of food insecurity on the university experience. We conducted individual semi-structured interviews with 11 international post-secondary students who had food insecurity, were enrolled at a public university in Canada, and who had requested emergency foodhampers from the on-campus food bank. Interviews were audio-recorded, transcribed verbatim, and analyzed using manifest, inductive content analysis. International post-secondary students reported several logistical issues related to obtaining sufficient food, including a lack of time, limited family support, modest food preparation skills, and low knowledge about supportive services and resources. Students also faced challenges in sourcing culturally appropriate foods, including issues related to food availability, accessibility, acceptability, and affordability. Further, they perceived food insecurity to negatively influence their academic performance through compromised concentration, reduced class and exam attendance, and adverse mpactson physical, mental, and social well-being. Some students reported extreme food deprivation, resulting in hunger. Our results revealed the negative impacts that food insecurity can have on international post-secondary students. Findings underscore the imperative to minimize the occurrence of food insecurity while studying in Canada by introducing and enhancing support systems on campus and in the community to enable food security.